Efectos del fracking y estrategias de las principales potencias en las caídas del precio del petróleo (2017)
This work was carried out with the objective of knowing the reasons why the world economic crisis may be affected or reflected in the introduction of new hydrocarbon extraction techniques. It was developed by identifying the characteristics of "fracking", what is its origin and what evolution it has had over the years. After this, reference is made to how this technique is reflected in Colombian competitiveness and that other factors contribute to it; It will take into account the economic strategies that countries of large exports are using to benefit from this global crisis. And finally we will talk about the changes that the oil price has suffered in recent years and how this affects the world economy and the relationship between countries.